An update on SARS-CoV-2 immunization and future directions - Rana, Rashmi; Kant, Ravi; Kumra, Tanya; Gupta, Sneha; Rana, Devinder Singh; Ganguly, Nirmal Kumar (Frontiers in Pharmacology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was discovered in Wuhan, China. Since it’s discovery, the virus has spread all over the world, and infected millions of people, and caused lakhs of deaths. Coronavirus is presently a dominating concern all over the world where different means like drugs and vaccines are being used to relieve the symptoms and prevent severe infections of coronavirus. SARS-CoV-2 infected patients could be asymptomatic, as well as patients could be symptomatic and can show several symptoms including fever, cough, and breath shortness. Scientist all over the world are doing hard efforts to eliminate this deadly virus. The harsh effects of Covid 19 on humanity and the economy of every country need next-generation vaccine development to end this virus completely from the world. In relation to this, various types of vaccines are produced varing in terms of their efficacy. Also, new variants of the virus are generating problem and also confusing about the efficacy of available vaccine so a proper comparision of these vaccine is needed. In this article, we compared the different available vaccines for their method of production, cost, dosage required and effectiveness .